EFEK PENYUNTIKAN PROSTAGLANDIN F2α (PGF2α) TERHADAP TIMBUL DAN LAMA BIRAHI SAPI BALI PADA PARITAS YANG BERBEDA - Abdul Malik (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
The objective of this study was to evaluate of Effect of injection Prostaglandin F2α on the time required for onset of estrus and estrus durations in Bali cattle with differences of Paritas. A total of 24 Bali cows were divided into four groups, each group was consisting of 6 cows.  Group 1 samples is heifer’s, group 2, samples was paritas1, group 3, samples was paritas 2 and group 4, samples was paritas 3.  All  cows were normal  tract of reproduction  with showing regular cyclic activities and having active of corpus luteum. The parameters in this study were determined including the time required for onset of estrus and duration of estrus. The result showed that percentage estrus response and duration of estrus were non-significant difference (P>0.05) between heifers and paritas 1, 2, and 3 after estrus synchronization with single dose of prostaglandin F2α. It was concluded that injection of PGF2α on heifers and Paritas 1,2 and 3 were  similar result on the time required for onset of estrus and duration of estrus.